Analysis of the Characteristics of Higher Order Thinking Skills (HOTS) Test on Momentum and Impulse for Senior High School Student Using Item Response Theory - Aulia Rahman; Heni Rusnayati; Muslim Muslim (Universitas Negeri Surabaya, 2021)
Currently, 21st-century skills are needed by students, especially Higher Order Thinking Skills (HOTS), to meet the needs of the rapidly growing world of work. It is necessary to provide debriefing during learning activities to meet these needs. Besides that, a quality instrument is needed to measure the skills of each student, the more information that the instrument can provide shows that the instrument is getting better. This study aimed to determine the characteristics of the Higher Order Thinking Skills test on momentum and impulse consisting of validity, reliability, difficulty level, and discrimination index based on item response theory analysis. The method used in this research is a descriptive method with a quantitative approach and a One-Shot Design research design. The population was second-year senior high school students in Bandung. Meanwhile, the sample of this study consisted of 122 second-year senior high school students who were selected using a purposive sampling technique. The instrument used was the Higher Order Thinking Skills test on momentum and impulse. Based on the result, 16 items were categorized as valid. Besides, the reliability of the test instrument was good. For the level of difficulty, an item was categorized as very difficult, an item was difficult, twelve items were medium, three items were easy, and an item was very easy. Lastly, for the discrimination index, thirteen items were considered good, and five items did not classify as good.